Short- and long-term mortality in severe sepsis/septic shock in a setting with low antibiotic resistance: A prospective observational study in a Swedish University Hospital - Anna eLinnér; Anna eLinnér; Jonas eSundén-Cullberg; Jonas eSundén-Cullberg; Linda eJohansson; Hans eHjelmqvist; Anna eNorrby-Teglund; Carl Johan eTreutiger; Carl Johan eTreutiger (Frontiers Media S.A., 2013)
Background: There is little epidemiologic data on sepsis, particularly in areas of low antibiotic resistance. Here we report a prospective observational study of severe sepsis and septic shock in patients admitted to the Intensive Care Unit (ICU) at Karolinska University Hospital, Sweden.We aimed to evaluate short and long-term mortality, and risk factors for sepsis related death. A second aim was to investigate patient care in relation to gender. Methods: 101 patients with severe sepsis and septic shock, admitted to the ICU between 2005 and 2009, were prospectively enrolled in the study. Defined primary endpoints were day 28, hospital and 1-year mortality. Risk factors for sepsis related death was evaluated with a multivariate analysis. In the subset of patient admitted to the ICU through the emergency department (ED), time to clinician evaluation and time to antibiotics were assessed in relation to gender. Results: In the septic cohort, the day 28, hospital and 1-year mortality rates were 19%, 29% and 34%, respectively. 93% in the septic cohort received adequate antibiotics from the beginning. Multiresistant bacteria were only found in three cases. Among the 43 patients admitted to the ICU through the ED, the median time to antibiotics was 86 minutes (IQR 52-165), and overall 77% received appropriate antibiotics within 2h. Female patients received antibiotics significantly later compared to male patients (p=0.02). Conclusions: The results demonstrate relatively low mortality rates among ICU patients with severe sepsis/septic shock, as compared to reports from outside Scandinavia. Early adequate antibiotic treatment and the low incidence of resistant isolates may partly explain these findings. Importantly, a gender difference in time to antibiotic therapy was seen.